Asserting public health interest in acting on commercial determinants of health in sub-Saharan Africa: insights from a discourse analysis. Issue 7 (11th July 2022) - Loewenson, Rene; Godt, Sue; Chanda-Kapata, Pascalina
Abstract : The actors influencing the commercial determinants of health (CDOH) in sub-Saharan Africa (SSA) have different interests and lenses around the costs and benefits of market influences in health. We analysed the views and priorities on CDOH in the discourse of global and regional agencies, SSA governments, private investors and companies, civil society and academia through a desk review of online publications post-2010, validated by purposively selected key informant interviews. The most polarised views were between civil society and academia on one hand, focused more on harms, and private business/investors on the other, almost exclusively focused on benefits. Others had mixed messaging, encouraging partnerships with commercial actors for health benefits and also voicing cautions over negative health impacts. Views also differed between transnational and domestic business and investors. Three areas of discourse stood out, demonstrating also tensions between commercial and public health objectives. These were the role of human rights as fundamental for or obstacle to engaging commercial practice in health; the development paradigm and role of a neoliberal political economy generating harms or opportunities for health; and the implications of commercial activity in health services. COVID-19 has amplified debate, generating demand for public sectors to incentivise commercial activity to 'modernise' and digitise health services and meet funding gaps and generating new thinking and engagement on domestic production of key health inputs. Power plays a critical role in CDOH. Commercial actors in SSA increase their influence through discursive and agential forms of power and take advantage of the structural power gained from a dominant view of free markets and for-profit commerce as essential for well-being. As a counterfactual, we found and present options for using these same three forms of narrative, agential and structural power to proactively advance public health objectives and leadership on CDOH in SSA.